A Study of Intense Local dB/dt Variations During Two Geomagnetic Storms. Issue 6 (15th June 2018) - Ngwira, Chigomezyo M.; Sibeck, David; Silveira, Marcos V. D.; Georgiou, Marina; Weygand, James M.; Nishimura, Yukitoshi; Hampton, Donald
Abstract: Interactions between the solar wind and the Earth's magnetosphere manifest many important space weather phenomena. In this paper, magnetosphere‐ionosphere drivers of intense d B /d t produced during geomagnetic storms that occurred on 9 March 2012 and 17 March 2015 are analyzed. A multi‐instrument approach combining Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission space‐borne and ground‐based observations was adopted to examine the magnetosphere‐ionosphere signatures associated with the d B /d t extremes during each storm. To complement the THEMIS measurements, ground‐based magnetometer recordings and All‐Sky Imager observations, equivalent ionospheric currents derived from magnetometer chains across North America and Greenland, and geosynchronous observations from the Los Alamos National Laboratory Synchronous Orbit Particle Analyzer are also examined. Our results show that the most extreme d B /d t variations are associated with marked perturbations in the THEMIS magnetospheric measurements, poleward expanding discrete aurora passing over the magnetometer sites (seen by the ground‐based THEMIS All‐Sky Imagers), intense Pc5 waves, rapid injection of energetic particles, and intense auroral westward currents. Substorms are considered as the major driver with a possible contribution from magnetospheric waves. The findings of this study strongly suggest that the localization of extreme d B /d t variations is most likely related to the mapping of magnetosphere currents to local ionospheric structures. Key Points: Magnetosphere‐ionosphere processes associated with local d B /d t extremes during storms are examined Intense d B /d t are confined to poleward edge of expanding aurora, a region with most active but localized magnetosphere energy conversion Substorms are considered as the major driver with a possible contribution from magnetospheric waves